SUSTAINABLE ANALYSIS OF AGRITOURISM-BASED TOURIST VILLAGES IN SLEMAN DISTRICT, INDONESIA - Zulfadli M.M.; Handayani S.M.; Setyowati (Russian Journal of Agricultural and Socio-Economic Sciences)
Agritourism-based tourist villages can provide economic benefits to local communities. However, developing sustainable agritourism-based tourist villages must also consider economic, ecological, and socio-cultural benefits. So that tourist villages can meet current needs without sacrificing future needs. Sleman Regency has the most significant tourist villages in the Special Region of Yogyakarta Province. This study aims to determine the sustainability status of agritourism-based tourist villages in Sleman Regency. The primary method used in this research is descriptive analysis, and the number of agritourism-based tourist villages studied is 14. In-depth information was obtained from key informants, including policymakers, associations, and heads of agritourism-based tourist village managers. Data were analyzed using Multi-Dimensional Scaling (MDS). The results of this study show that the economic dimension (69.95) is entirely sustainable, the ecological dimension (90.45) is sustainable, the socio-cultural dimension (70.94) is entirely sustainable, and the facilities and infrastructure dimension (73.07) is entirely sustainable.